Pressure-Induced Order Transition in Nanodot-Forming Diblock Copolymers at the Air/Water Interface - Perepichka, Iryna I; Borozenko, Kateryna; Badia, Antonella; Bazuin, C. Geraldine (Journal of the American Chemical Society, 2011)
Understanding and controlling the processes in block copolymer (BC) monolayers at the air/water interface during surface area compression is a key issue for producing ultrathin films of predetermined morphology with well-defined order and known dimensions. Langmuir isotherms of nanodot-forming BC monolayers generally display a plateau indicative of a 2D phase transition, which has been the subject of various interpretations in the literature. Here, based on investigations of Langmuir–Blodgett and Langmuir–Schaefer nanodot films of PS-P4VP mixed with 3-n-pentadecylphenol (PDP), we show by atomic force microscopy (AFM) that it involves a change in nanodot packing order (from quasi-hexagonal to quasi-square), argued to be a general phenomenon for nanodot BC monolayers. It is accompanied by system-specific conformational changes (as discussed in previous literature), which, in the present case, implicate PDP alkyl chain ordering, as deduced previously from in situ infrared data and indirectly supported here by AFM imaging.